A study on the relationship between emotional intelligence and job satisfaction among employees in selected companies - Shashikumar, C R; Madhusudhan, T K; Karthik, N; Rajath, H S (The International tax journal, 2026)
The present study investigates the relationship between emotional intelligence and job satisfaction among employees working in selected companies. The study adopts a descriptive and analytical research design with a quantitative and cross-sectional approach. Primary data were collected from 182 employees working in Infosys Ltd., Wipro Ltd., Tata Consultancy Services, Accenture India Pvt. Ltd., and HCL Technologies Ltd. using a structured questionnaire based on a five-point Likert scale. Descriptive statistics, Cronbach's alpha, Pearson correlation, Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM) were employed for analysis. The findings revealed that emotional intelligence and job satisfaction recorded mean values of 4.18 and 4.06 respectively. Correlation analysis indicated significant positive relationships between emotional intelligence dimensions and job satisfaction, with motivation showing the strongest association (r = 0.801). SEM results confirmed that motivation (β = 0.386) had the highest influence on job satisfaction, followed by social skills (β = 0.354) and empathy (β = 0.297). Hypothesis testing results revealed significant positive relationships and influences, leading to the rejection of both null hypotheses. The findings confirm that emotional intelligence significantly enhances job satisfaction among employees. The study concludes that emotional intelligence enhances employee satisfaction and organizational effectiveness.